Capacity Building for Engineering Training and Technology via STEAM Education - Damira Jantassova; Daniel Churchill; Olga Shebalina; Dinara Akhmetova (MDPI AG, 2022)
This paper reports the "Capacity building for innovative engineers through STEAM education" project conducted at Kazakhstan's Saginov Technical University ('STU') and funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AR09260338). The problem of intercultural communication and the ability to collaborate, the issues of critical thinking development, and using the creative approach to solving professional tasks remain weak in the system of engineering higher education in Kazakhstan. STEAM Education appears to serve a role in overcoming the problem. Conducting a comprehensive study of the world experience and developing strategies for introducing STEAM into the educational process at Kazakhstani universities based on multifactor SWOT analysis made it possible to form several STEAM approaches for innovative engineering education. In the paper, we present the STEAM (Science-Technology-Engineering-Arts-Mathematics) Education framework for innovative training of engineers developed based on the best practices from around the world. This framework focuses on sustainable engineering education for intercultural communication, creative industry, and creative cooperation. In developing the STEAM Education framework, the researchers applied a methodology that included classification and comparison of international STEAM Education practices, analysis of regulatory documents, and statistical data in the sphere of education and multifactor SWOT analysis.